2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34855
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Unmanned Aerial Vehicles and Aerial Photogrammetry into a Civil Engineering Course to Enhance Technology Competency

Abstract: Given the increasing use of technology in civil engineering, it is important for students to be proficient in learning and using new technologies. In academic settings, this priority translates into students gaining experience using technology and learning about potential applications. Since technology evolves, it is more important to cultivate technology competency in students than to teach specific technologies, software, coding languages, etc. In this project, our objective was to integrate technology into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…External sensors such as cameras, LiDAR, SONAR, temperature sensors, and proximity sensors vary in size, mission, and range. Cameras play a vital role in providing real-time mission information, while UAVs can also transport water and chemicals for crop spraying [51], [52].…”
Section: Componentsmentioning
confidence: 99%
“…External sensors such as cameras, LiDAR, SONAR, temperature sensors, and proximity sensors vary in size, mission, and range. Cameras play a vital role in providing real-time mission information, while UAVs can also transport water and chemicals for crop spraying [51], [52].…”
Section: Componentsmentioning
confidence: 99%
“…Molina et al (2014) invited an interdisciplinary team of undergraduate engineering students to collaborate and provide solutions to the drones’ range and endurance issues. Very recently, Camarillo et al (2020) integrated drones and photogrammetry in a civil engineering course in order to improve the students’ technology exposure and competency. Despite these attempts, real-world drone training remains a difficult task.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, researchers indicated that real-world drone training is associated with the risk of inflight drone crash, especially since mistakes are always part of the learning process (Weldon and Kozak, 2017). For example, Camarillo et al (2020) indicated that students were not involved in the drone flight mission and only observed the data collection workflow, correlating the successfulness of their real-world drone flight with the experience of the drone pilot. In addition, others stated that the risk of inexperienced pilots causing serious accidents in actual drone flights is significant (De la Torre et al , 2016), not to mention the potential monetary damage and struck-by risks associated with drone training over people (Bu et al , 2015).…”
Section: Introductionmentioning
confidence: 99%